Beyond tomorrow ([Place of publication not identified] Digiview Productions, 2004)
Three wealthy heads of an engineering firm decide to do a little matchmaking. Growing older and lamenting the lonely existence brought on by the demands of business, the bored trio concoct a plan to invite two strangers over to their mansion for Christmas dinner. Soon enough the strangers fall in love and become friendly with the wealthy matchmakers. A tragic plane crash however takes the lives of the trio, leaving the couple to carry in by themselves. In time, circumstances conspire to come between the couple and it is at this point that trio come back into the picture as ghosts. Before going to Heaven, it seems, the spirits must find a way to help the couple find each other again.
A supernatural story filled with holiday spirit.
Harry Carey Sr., Aubrey Smith, Charles Winninger, Richard Carlson, Jean Parker.
DVD ; Standaard full frame ; Stereo Sound.
In English.